LEARNING ISLAMIC MODERATION IN PESANTREN: The Construction of Kiai’s Thought about Islamic Moderation and Its Implication on The Students’ Behavior - Siswanto, Siswanto; Ahmad Fawaid; Saiful Hadi (Islamuna: Jurnal Studi Islam, 2024)
The study of Islamic moderation in pesantren needs to be considered as an effort to prevent radicalism and extremism, because besides having historical legitimacy as indigenous Indonesian education, pesantren since its inception have affirmed itself as a moderate education. By using a qualitative approach, the research which was carried out in four Islamic boarding schools in Madura resulted in the construction of the kiai's moderation thought is in the neo-modernist type. Islamic moderation is instilled by promoting exemplary and learning from walisongo, as well as being given understanding through studying the turats book. It is manifested in tolerant behavior and openness to ikhtilaf. The implication for the santri's diversity is the growth of respect for religious differences and opinions within their own religion.